Inteligencia emocional y aprendizaje significativo, en tiempos de pandemia, en los niños de educación primara, Puno - 2021 - Turpo Quispe, Clemente (2023)
The general objective of this research was to determine the relationship between emotional intelligence and meaningful learning, in times of pandemic, of children in the fifth grade of primary education, in an Educational Institution in Puno, 2021. It is a basic type of research with descriptive-correlational design. The sample consisted of 34 children in the fifth grade of primary education, in an Educational Institution of Puno, 2021, the research technique was observation and its instrument was the checklist. Instrument that were validated by expert judgment. The result that corresponds to the general objective is that, between emotional intelligence and meaningful learning, there is a significant relationship (p<.05), direct and to a low degree (r=.167). In this way, the null hypothesis is rejected and the alternative hypothesis is accepted: There is a significant relationship between emotional intelligence and meaningful learning in fifth grade children of primary education, in an Educational Institution of Puno, 2021.